Morphology of the Oligoryzomys nigripes respiratory system. (4th June 2018) - Mario, Lara Carolina; Borghesi, Jéssica; G. Hayashi, Rafael; O. Favaron, Phelipe; N. Rodrigues, Marcio; C. Carvalho, Rafael; Miglino, Maria A.
Abstract: Rodents are important in the transmission of infectious diseases that affect the respiratory tract, including simple infections and those caused by specific pathogens. These animals are natural reservoirs of zoonoses that cause many public health diseases. Basic knowledge on the morphology of these animals is important as basic research is useful for applied studies, such as the development of clinical, therapeutic, surgical and clinical models. Morphological data of respiratory tract in Oligoryzomys nigripes are absent in the literature. Therefore, the aim of this study was to perform a morphological analysis of the respiratory tract of O. nigripes . Five adult females from the environmental reserve in São Joaquim da Barra, São Paulo were used, donated to the Museum of Veterinary Anatomy (FMVZ/USP). Several morphological features follow the same pattern seen in rodents; however, this species showed some differences such as the presence of three lobar bronchi, nonlobed left lung and the right lung constituted by two lobes. Respiratory epithelium lined the whole respiratory tract and was seen using scanning electron microscopy the oval shape of the parenchyma and alveoli.